Estimating economic losses due to pasture weeds - Bourd?t, G.W.; Saville, D.J. (New Zealand Plant Protection, 2002)
A method is presented for estimating the economic loss sustained by a pastoral industry due to a nonpalatable herbaceous weed The method requires monthly estimates of weed ground cover and dry matter produced by noninfested pasture along with the per annum production revenue and an estimate of the percentage of the industrys pastureland infested by the weed Applied to giant buttercup (Ranunculus acris L) in dairy pastures in New Zealand the method estimated the national economic loss due to this weed to be NZ 118 million in the 19992000 year